Life-cycle assessment of typical Portuguese cork oak woodlands - González-García, Sara (2018)
Cork forest systems are responsible for making an important economic contribution to the Mediterranean region, especially Portugal where the cork oak woodlands or montados contain about 32% of the world's area. The environmental profile derived from reproduction cork production and extraction in two Portuguese regions (Tagus valley and Alentejo) representative of the Portuguese sector were assessed in detail using the Life-Cycle Assessment (LCA) methodology from a cradle-to-gate perspective. The production line was divided into four stages considering all the processes involved: stand establishment, stand management, cork stripping and field recovery. According to the environmental results, there were remarkable differences between the two production scenarios mainly due to the intensity and repetition of forest activities even though the cork yield was reported to be the same. The management system in the Alentejo region presented the worse environmental profile in almost all the impact categories under assessment, mainly due to the shorter cycle duration of the mechanical cleaning and pruning processes. Cork stripping was identified in both scenarios as the production stage with the highest contribution to the environmental profile due to the cleaning and pruning processes. A sensitivity assessment concerning the cork yield was performed since the average production yields in the Portuguese montados are lower than the ones used in this study. Thus, if the cork yield is reduced, the environmental profile in both scenarios gets worse since almost all the forest activities involved are the same.